Analysis of the effect of filtering elements on EEG and EMG recorded with high sensitivity channel based on nanoelectrodes; Biology and Medicine; Vol. 6, iss. 2 - Avdeeva D. K. Diana Konstantinovna; Turushev N. V. Nikita Vladimirovich; Ivanov M. L. Maxim Leonidovich; Yuzhakova M. A. Maria Aleksandrovna; Grigoriev M. G. Mikhail Georgievich (2014, 2014)
Title screen